Hubungan Pengetahuan Dan Sikap Perawat Tentang Infeksi Nosokomial Dengan Perilaku Hand Hygiene di Rumah Sakit X Yogyakarta - Florianus Hans Matheus Mawo; Erlangga Mandala Sakti; Akbar Amin Abdullah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Background:Hand hygiene is an effective step to break the chain of infection transmission, so that nosocomial incidence can be reduced. Infection prevention and control absolutely must be carried out by nurses, doctors and all people involved in patient care. Nurses' hand hygiene behavior is one of the factors that has a big influence on preventing nosocomial infections in hospitals. At Hospital X in 2014 the proportion of phlebitis incidents was 6.5%. Phlebitis is a nosocomial infection. The results of observations of four nurses who carried out medical procedures, one of them did not wash his hands before and after carrying out procedures on patients, while the other three had already washed their hands. Research Objective: To determine the relationship between nurses' knowledge and attitudes about infections nosocomial with hand hygiene behavior at Hospital Data analysis used the Chi-square test with a confidence level of 95% (α= 0.05). Research Results: Characteristics of nurses at Hospital 56.7%). Most of them were women, namely 25 nurses (83.3%). The most work period is 1-5 years (56.7%). The highest level of education was D3 nursing (93.3%). Good knowledge about nosocomial infections was 26 nurses (86.7%). Most of the attitudes were positive, namely 27 (90.0%) nurses. Most of them had good hand hygiene behavior19 (63.3%). There is a relationship between nurses' knowledge about nosocomial infections and hand hygiene behavior with a p value of 0.012 (p<0.05). There is a relationship between nurses' attitudes and hand hygiene behavior p of 0.041 (p<0.05). Conclusion: There is a relationship between nurses' knowledge about nosocomial infections and hand hygiene behavior and there is a relationship between nurses' attitudes and hand hygiene behavior.